Simulation of evacuation in an inclined passenger vessel based on an improved social force model. (April 2022) - Fang, Siming; Liu, Zhengjiang; Wang, Xinjian; Wang, Jin; Yang, Zaili
Highlights: The influence of heeling on individual's walking speed is greater than trim. It is the best condition for evacuation when the inclination angle is less than 20°. A small inclination angle speeds up the evacuation process. Evacuation time increases as the number of pedestrians increases. Abstract: Passenger vessels often present different heeling and/or trim angles during and after accidents, while recognising it as the main factor affecting pedestrian movement during an emergency evacuation process, there is difficulty to reproduce the evacuation activities on ships due to cost constrains and safety concerns in relevant studies. To fill the research gap, an improved social force model (SFM) incorporating both inclining and self-adjusting forces of pedestrians into the basic SFM model was constructed to simulate the pedestrian dynamics under different ship trim and heeling circumstances. The improved SFM also includes a reduction law of pedestrian speed at different heeling and/or trim angles and adds a calculation of the reduction factor in each time step. It enables the simulation of the pedestrian movement process on inclined vessels accurately. The simulation results show that when the inclination angle is less than 20°, the impact of both heeling and/or trim on an individual's walking speed and evacuation time are weaker than the one with an angle exceeding 20°. When passengers walk along the keel line on an inclined ship, the impact of heeling on speed attenuation is more significant than the one of trim. The overall evacuation time is extended with the increasing number of evacuees. The flow rate at the exit reaches the maximum when the number of evacuees is 100, and the average evacuation rate is 2.01 persons/s. The findings provide useful insights on crowd management in the process of passenger vessel evacuation under an inclined state.